Virtual community-based interventions for family caregivers of people with dementia: A scoping review protocol - Yifan Wang; Lei Zhao; Fangyu Zou; Hangyu Zhou; Xiaoyan Li; Caifu Li; Linyan Xu (PLoS ONE, 2026)
Introduction Family caregivers provide the majority of long-term care for people with dementia and often experience substantial psychological distress, social isolation, and caregiving burden. With the rapid development of digital technologies, virtual communities—platforms that enable interaction, information exchange, and emotional support—have emerged as a potential approach to support dementia caregivers. However, evidence regarding technological forms, content components and outcomes remains fragmented and heterogeneous. This scoping review aims to systematically map the existing evidence on virtual community-based interventions for family caregivers of people with dementia. Methods This protocol follows the Joanna Briggs Institute methodological framework for scoping reviews and will adhere to the PRISMA-P guidelines. The ‘Population-Concept-Context’ framework will guide eligibility determination. Empirical studies involving family caregivers of people with dementia and describing interventions delivered through interactive virtual communities will be eligible. We will systematically search eight databases. Grey literature sources will also be searched. Two reviewers will independently screen the literature and extract data using an iteratively refined charting tool focusing on technological forms, content components, and outcomes. Findings will be synthesized through descriptive mapping and qualitative content analysis. Discussion To our knowledge, based on preliminary searches, this appears to be the first scoping review to focus specifically on virtual community-based interventions targeted at dementia family caregivers. Findings will provide a comprehensive overview of technological forms, content components, and outcomes, offering essential insights for the design, implementation, and evaluation of future virtual community interventions.